(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Poultry production, though a very lucrative venture, is being marred by diverse challenges, including infectious diseases. In the poultry industry, Newcastle disease (ND) is often complicated by Escherichia coli and Ascaridia galli. This case report described the diagnosis and management of these diseases in a flock of one-year-old Isa Brown layer chickens with complaints of increasing mortality and a decrease in egg production. The clinical case was diagnosed and treated based on the results of postmortem findings, and diagnostic work-up including pericarditis, congested and friable liver, misshapened and pedunculated ovarian follicles, necrotic caecal tonsils, egg yolk peritonitis, petechial haemorrhages on and erosion of proventricular mucosae, low protective antibody (26%), and identification of Ascaridia galli from the small intestine, and E. coli from sampled organs. The flock was treated with 20% Enrofloxacin at 1 mL/2 L, plus povidone (10% iodine) at 1 mL/2 L, and 10% Mebendazole at 1 g/L, all administered in drinking water for five consecutive days, followed by two consecutive days. Ten days post-treatment, mortality rates plummeted, and egg production resumed its peak. These findings demonstrate that a combination of diagnostic work plans, including postmortem examination, microbial culture, and antibiotic susceptibility testing, as well as the haemagglutination inhibition test, is reliable for diagnosing and managing natural concurrent infections associated with ND, colibacillosis, and ascaridiasis.